Estudo exploratório sobre compatibilização semântica devocabulário utilizando ontologia: fundamentação teórica-metodológica visando ao aperfeiçoamento do MHTX - Eliana Antonia Demarques (2011)
This is a exploratory study regarding semantic vocabulary compatibilization utilizing the MHTX[1] ontology, contemplating reading and writing practices of published documents in digital libraries. Within these environments, the vocabulary ambiguity is stressed as one of the crucial aspects for the semantic compatibilizing of heterogeneous bases. The integration of conceptual models is one of the most used techniques to share information with a common understanding among terminological conceptual meanings. The MHTX supports the creation of an interactive environment. The idea is to analyze the representation of different publications in a unique map with an integrated conceptual system, using as an underlying concept the methodological-theory about vocabulary compatibilization, aiming at the improvement of the MHTX. A new technique of digital objects representation is presented considering the very same principles of faceted classification. This technique allowed using the concepts functionalities to explain the equivalence relationships in a unique map,meeting the assumed ideas of this study that stresses a concept of descriptive, administrative and structural metadata. Therefore both indexation and retrieval shall be based in a terminological agreement for the establishment of formal categories directly connected to the languages use. The combination of these categories represented in domain ontologys facets showed semantic connections, in which the expressedcharacteristics in hyper-textual objects are present in the definition and relationships among these hyperlinked objects. The results confirm the viability of inserting MHTX domain ontology, using the proposed modeling with automated mechanisms of indexation to conduct the compatibilization semantic vocabulary.